Recent Advancements in Cloud Computing - Thakur, Ramesh (International Journal of Computer Sciences and Engineering, 2014)
The delivery of computing services like servers, storage, databases, networking, software, analytics, and intelligence on the Internet is termed as cloud computing. The aim is to provide quick innovation, flexible resources, and economies of scale. The information that the user wants to access is stored in clouds. It is not necessary that the user should be at a specific place for accessing these clouds. Various organizations may find cloud technology affordable as it allows them to reduce the cost associated with management of information. The organizations do not need to keep their own servers and can use capacity rented from third parties. Cloud allows organizations for fast software updation as compared to other technologies.